267 ACCURACY OF PERINEAL LACERATION REPORTING IN ADMINISTRATIVE AND CLINICAL DATA AT AN ACADEMIC MEDICAL CENTER. Issue 1 (1st January 2007) - Shaffer, R. M.; Benedetti, T. J.; Wilson, J.
Abstract : Objective: Perineal lacerations are a cause of significant morbidity following vaginal deliveries. Indeed, the rates of third- and fourth-degree perineal lacerations are now reported to national hospital auditing bodies, such as the Joint Commission on Accreditation of Healthcare Organizations (JCAHO), as a quality control measure. The purpose of this study was to evaluate the rates of third- and fourth-degree perineal lacerations at the University of Washington Medical Center (UWMC) and to determine the accuracy of their reporting. Methods: This study was constructed as a retrospective chart review. We included in our study all women who delivered at the UWMC between 7/1/99 and 6/30/05. Calculations of the total number of births included all women who delivered via spontaneous vaginal, cesarean, operative, or breech routes. Diagnoses of third- and fourth-degree vaginal lacerations were confirmed for individual patients by comparing the diagnosis in the clinical postpartum electronic medical record summary with the administrative ICD-9 billing code recorded for the patient. If discrepancies were found, the patient's entire clinical chart was examined and data were reconciled if possible. Results: Third- and fourth-degree perineal lacerations were reported accurately overall, with a total of 488 of 10, 511 total births (4.3%) flagged as resulting in third- or fourth-degree lacerations in either the clinical or the administrative databases. Of these, 165 appeared in only one of the databases, and this discrepancy was evaluated further by examining the patient's primary clinical chart. From this disputed pool, 94 cases could be resolved and 71 remained unresolved. Of the 71 unresolved cases, 29 appeared in the administrative database only and 45 appeared in the clinical database only. After all the data were cleaned in this way, it was determined that 406 (3.9%) of the deliveries were reported to JCAHO, whereas 422 (4.0%) of the deliveries resulted in significant lacerations in the actual clinical setting. Conclusion: Preliminary data suggest that third- and fourth-degree perineal lacerations at the University of Washington are adequately reported to JCAHO, validating this measurement as a form of quality control.